2011
DOI: 10.1111/j.1574-6968.2011.02435.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of bacteria with different mechanisms for chitin degradation result in the formation of a mixed-species biofilm

Abstract: In this study, interactions between bacteria possessing either released or cell-associated enzymes for polymer degradation were investigated. For this, a co-culture of Aeromonas hydrophila strain AH-1N as an enzyme-releasing bacterium and of Flavobacterium sp. strain 4D9 as a bacterium with cell-associated enzymes was set up with chitin embedded into agarose beads to account for natural conditions, under which polymers are usually embedded in organic aggregates. In single cultures, strain AH-1N grew with embed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
(44 reference statements)
1
13
0
Order By: Relevance
“…Most experimental research examining social evolution in bacterial populations has been performed with liquid cultures, which eliminate population spatial structure that is ubiquitous in realistic environments [1, 2] and is predicted to be critical for the evolution of cooperation [20-24]. Social evolution has been studied in radially expanding colonies on agar, but no general mechanisms have been found that show how enzyme-producing cells avoid exploitation by non-producers in biofilms [8-11, 25, 26]. Given that biofilms are the dominant form of bacterial life in nature, and that many bacterial species secrete digestive enzymes, clarifying the means by which cooperative cells avert exploitation in biofilms is a major outstanding problem.…”
Section: Resultsmentioning
confidence: 99%
“…Most experimental research examining social evolution in bacterial populations has been performed with liquid cultures, which eliminate population spatial structure that is ubiquitous in realistic environments [1, 2] and is predicted to be critical for the evolution of cooperation [20-24]. Social evolution has been studied in radially expanding colonies on agar, but no general mechanisms have been found that show how enzyme-producing cells avoid exploitation by non-producers in biofilms [8-11, 25, 26]. Given that biofilms are the dominant form of bacterial life in nature, and that many bacterial species secrete digestive enzymes, clarifying the means by which cooperative cells avert exploitation in biofilms is a major outstanding problem.…”
Section: Resultsmentioning
confidence: 99%
“…No interactions were observed (data not shown). Millimolar concentrations of NAG are commonly observed in nature suggesting that in such environments AHL-mediated gene expression will be repressed (Gorke and Stulke, 2008; Eisenreich et al, 2010; Frimmersdorf et al, 2010; Jagmann et al, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…NAG is the monomer of the second most abundant biopolymer on Earth and is also a major component of heterogeneous polysaccharides including murein and hyaluronic acid. It is commonly encountered in the environment in millimolar concentrations (Jagmann et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The A. hydrophila strain AH-1 is able to degrade chitin due to extracellular chitinases, and Flavobacterium sp. acts as a cheater that uses chitin degradation products as nutrients (Jagmann et al, 2012). The biofilm formation of Aeromonas was enhanced when co-cultured with a Bacillus cereus strain that improves aggregation between bacteria (Cheng et al, 2014).…”
Section: Biofilm Formation In Aeromonasmentioning
confidence: 99%